The Blind Child During Early Childhood (0-3 Years) and the Educational Intervention - Argiropoulos, Dimitris (Psychological Counseling and Psychotherapy, 2020)
This article aims at approaching the role of education in accompanying the growth of blind children from early childhood. Blindness has several impacts on the juridical, medical, social and educational plans, which concur in defining the blind person, together with the individual features and cultural contexts in which the person lives. Here we will focus on the first years of life, to understand the most crucial factors in the development of the blind child from an educational perspective. The article puts forward a multidisciplinary educational method, where an equipe should take care of the blind child and elaborate objectives together with the family. Communication among adults observing the child in different life contexts is particularly important, allowing timely compensation interventions. An attitude of continuous observation and mediation with the family allows an authentic child-centered approach.